Intergranular aragonite cement as evidence for widespread cryogenic brine formation during Quaternary glaciation in the McMurdo Sound region, Antarctica. (15th January 2020) - Yang, Mingyu; Frank, Tracy D.; Fielding, Christopher R.
Abstract: Briny groundwater is present below the extremely cold and dry surface of the McMurdo Dry Valleys and below the seafloor of the adjacent McMurdo Sound in Antarctica. The lack of reliable groundwater samples in the region, however, has long limited understanding of its origin, nature, and spatial distribution. In this regard, intergranular carbonate cements, widespread in subsurface Cenozoic strata and recently recognized as brine precipitates, provide an indirect means of solving these issues. This study examines the petrography and isotope geochemistry of intergranular aragonite cement phases that occur in subsurface Pliocene-Quaternary sedimentary sections that formed in the lower Taylor Valley (cores DVDP-10, -11) and in offshore McMurdo Sound (core AND-1B). Aragonite cement in the coastal Taylor Valley sections is characterized by very low δ 18 O values (−26.9 to −19.4‰ VPDB) compared to values in the offshore section (−12.5 to −2.7‰ VPDB). These differences are interpreted to reflect two settings for cryogenic brine formation, which produced isotopically distinct brines during Quaternary glaciation. In the coastal region, seawater-meltwater mixtures were isolated and cryogenically concentrated in an ice-dammed lake setting that formed in response to the expansion of the East and West Antarctic Ice Sheets into the lower Taylor Valley. In McMurdo Sound, cryogenic concentration of seawater occurred in a semi-isolated flexural trough that was deepened by lithospheric depression of volcanic edifices and the expanded West Antarctic Ice Sheet. Aragonite cement phases serve as excellent proxies for tracing the extents of subsurface brine bodies along the continental margin of Antarctica. Given the propensity for cryogenic brine formation in glaciomarine settings, the likelihood of brine cements in rock records from other analogous high-latitude, cold settings must not be overlooked.